Epidemiologia de infecções relacionadas à assistência à saúde causadas por bacilos gram-negativos em Uberlândia - MG - Dias, Vinícius Lopes (2023)
The concern about the rapid emergence and spread of resistant microorganisms is growing in Brazil and worldwide, as the clinically available therapeutic options for treating infections caused by these microorganisms are limited, resulting in high mortality rates. The epidemiology and control of infections caused by resistant bacteria can be facilitated by epidemiological analysis as well as molecular analysis of these strains. Thus, this study sought elements to understand the epidemiology of healthcare-associated infections (HAIs) caused by Gram-negative bacilli (GNB) in the last 10 years, including the analysis of resistance, virulence, and dissemination genes of carbapenem-resistant K. pneumoniae strains in the city of Uberlândia. The data evidenced an increase in the incidence of HAIs in the last decade, as well as a high rate (67.4%) of carbapenem resistance in the three main species of Gram-negative bacilli (Acinetobacter baumannii, K. pneumoniae, and Pseudomonas aeruginosa) causing HAIs. Collected data also revealed that the infection rates for these three microorganisms increased approximately sixfold between 2011 and 2018. Regarding the presence of resistance and virulence genes in K. pneumoniae strains, it was observed that 47.9% (79), 10.9% (18) and 72.7% (120) carried the blaKPC, blaNDM, and blaVIM genes, respectively, while 91.8% simultaneously carried the entb, kfu, ureA, and wabG genes. As for the clonal analysis of a group of 15 selected isolates from these 165 samples, the similarity analysis detected the presence of five clonal patterns (A-E), with pulsotype B being the most prevalent, facilitating the understanding of the dynamics of dissemination of this resistant strain in the hospital environment. The results of this study highlight an alarming frequency of microorganisms such as A. baumannii (41.5%), P. aeruginosa (29.9%), and carbapenem-resistant K. pneumoniae (28.6%), representing a significant threat to healthcare services, as this resistance is associated with a poor prognosis. HAIs caused by multidrug-resistant microorganisms, particularly K. pneumoniae, represent a significant challenge in terms of infection control and treatment for both hospitalized and non-hospitalized patients in the ICU, as evidenced by the findings of this study. The transmission characteristics and the resistance and virulence mechanisms associated with this pathogen deserve more attention and investigation.